Antenatal and delivery practices and neonatal mortality amongst women with institutional and non-institutional deliveries in rural Zimbabwe: observational data from a cluster randomized trial - Christie Noble; Ciaran Mooney; Rachel Makasi; Robert Ntozini; Florence D. Majo; James A. Church; Naume V. Tavengwa; Andrew J. Prendergast; Jean H. Humphrey; for the Sanitation Hygiene Infant Nutrition Efficacy (SHINE) (BMC, 2022)
Abstract Background Despite achieving relatively high rates of antenatal care, institutional delivery, and HIV antiretroviral therapy for women during pregnancy, neonatal mortality has remained stubbornly high in Zimbabwe. Clearer understanding of causal pathways is required to inform effective interventions. Methods This study was a secondary analysis of data from the Sanitation Hygiene Infant Nutrition Efficacy (SHINE) trial, a cluster-randomized community-based trial among pregnant women and their infants, to examine care during institutional and non-institutional deliveries in rural Zimbabwe and associated birth outcomes. Results Among 4423 pregnant women, 529 (11.9%) delivered outside a health institution; hygiene practices were poorer and interventions to minimise neonatal hypothermia less commonly utilised for these deliveries compared to institutional deliveries. Among 3441 infants born in institutions, 592 (17.2%) were preterm (< 37 weeks gestation), while 175/462 (37.9%) infants born outside health institutions were preterm (RR: 2.20 (1.92, 2.53). Similarly, rates of stillbirth [1.2% compared to 3.0% (RR:2.38, 1.36, 4.15)] and neonatal mortality [2.4% compared to 4.8% (RR: 2.01 1.31, 3.10)] were higher among infants born outside institutions. Among mothers delivering at home who reported their reason for having a home delivery, 221/293 (75%) reported that precipitous labor was the primary reason for not having an institutional delivery while 32 (11%), 34 (12%), and 9 (3%), respectively, reported distance to the clinic, financial constraints, and religious/personal preference. Conclusions Preterm birth is common among all infants in rural Zimbabwe, and extremely high among infants born outside health institutions. Our findings indicate that premature onset of labor, rather than maternal choice, may be the reason for many non-institutional deliveries in low-resource settings, initiating a cascade of events resulting in a two-fold higher risk of stillbirth and neonatal mortality amongst children born outside health institutions. Interventions for primary prevention of preterm delivery will be crucial in reducing neonatal mortality in Zimbabwe. Trial registration The trial is registered with ClinicalTrials.gov, number NCT01824940.